Impact of Non-Performing Loan on Profitability of Banks in Bangladesh: A Study from 1997 to 2017 (Global Journal of Management and Business Research, 2019)
Bangladesh being a developing country heavily depends on the banking sector for smooth financial intermediation. Banking industry of Bangladesh has been facing the acute problem of NPL since long. This paper aims to discover the impact of non-performing loan ratio, capital adequacy ratio and provision maintenance ratio on the return on asset (ROA) of all banks based on the last twenty-one years data. This study also investigates the root causes and adverse effects of the non-performing loan. Secondary sources of data are collected from the annual reports of Bangladesh Bank and analyzed by Ordinary Least Square (OLS) method and Vector Auto Regression (VAR) model using STATA 14.2. The results of the study reveal that there are different directional short-run causality exist between variables and the OLS regression analysis confirms that two independent variables; non-performing loan ratio and provision maintenance ratio are statistically significant to the dependent variable; return on asset (ROA).
Keywords: non-performing loan; profitability; banks; bangladesh